A Case of Recurrent Proliferative Glomerulonephritis with Monoclonal IgG Deposits after Kidney Transplant Treated with Plasmapheresis - Ranghino, Andrea (S. Karger AG, 2012)
Proliferative glomerulonephritis with monoclonal IgG deposits (PGNMID) is a rare and recently identified disease with a poor prognosis irrespective of the treatment. Recently, the possibility of recurrent or de novo PGNMID after kidney transplantation has been reported, which is associated with a better prognosis compared to PGNMID on native kidneys. Nevertheless, at present, due to the very few cases of recurrent PGNMID diagnosed, there is no proven effective treatment. Here, we report a case of recurrent PGNMID successfully treated with plasmapheresis, steroids and mycophenolate mofetil. Our report suggests that plasmapheresis might be a valid therapeutic option to treat recurrent PGNMID.